UP in Mindanao online bioinformatics system - Bungao, Cheryl Villanueva (2006)
This software entitled ?UP in Mindanao Online Bioinformatics System? integrates the three programs completed by the BS Computer Science graduates of UP in Mindanao and made it online. These programs are the Parallel Computation of Nucleotide Mutation and Divergence Time Inferred from Phylogenetic Tree using Maximum Likelihood Method (Nucleotide MDT Computation) developed by Clarito (2003), the Working Space for Sequence Alignment and Detecting Informative Sites (WSSADIS) by Polinar (2005), and the Computation and Visualization of Synonymous and Nonsynonymous Substitution (CVSNOS) by Dumajel (2005). Its point and click interface provides an easy way of using and navigating the three programs. Features and functions of the three programs are still the same but interfaces were changed to make them viewable online. This software was developed as a contribution to molecular biology by creating an efficient tool for the researchers. The system was implemented using Apache Tomcat Server and Java Applet Technology
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2006
Keywords: UP in Mindanao; Bioinformatics; Bioinformastics system; Software designing